2011
DOI: 10.1186/1756-0500-4-68
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the hypoxia-inducible factor 1 alpha gene in Mexican patients with preeclampsia: A case-control study

Abstract: BackgroundAlthough the etiology of preeclampsia is still unclear, recent work suggests that changes in circulating angiogenic factors play a key role in its pathogenesis. In the trophoblast of women with preeclampsia, hypoxia-inducible factor 1 alpha (HIF-1α) is over-expressed, and induces the expression of non-angiogenic factors and inhibitors of trophoblast differentiation. This observation prompted the study of HIF-1α and its relation to preeclampsia. It has been described that the C1772T (P582S) and G1790A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Additionally, endochondral ossification process is triggered by the development of osteophytes. WISP-1 is an osteogenic factor and an osteoblast differentiation factor that has been studied in OA models, in which an increase in its expression was reported [ 32 , 33 ]. WISP-1 is a member of the CCN family of connective tissue growth factors, which also includes WISP-2 and WISP-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, endochondral ossification process is triggered by the development of osteophytes. WISP-1 is an osteogenic factor and an osteoblast differentiation factor that has been studied in OA models, in which an increase in its expression was reported [ 32 , 33 ]. WISP-1 is a member of the CCN family of connective tissue growth factors, which also includes WISP-2 and WISP-3.…”
Section: Discussionmentioning
confidence: 99%
“…It have been described polymorphic variants within the HIF1A gene; for example, the rs11549465 (P582S), and rs11549467(A588T) single-nucleotide polymorphisms (SNPs) are located in exon 12, on 14 th chromosome and influence the transcriptional activity of this gene to increase dramatically in comparison with the common isoform [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that the C1772T (P582S) and G1790A (A588T) polymorphisms of the HIF-1α gene under normoxic and hypoxic conditions show a higher transcriptional activity correlated with the overexpression of the corresponding protein than the transcriptional activity and protein expression of the wild-type sequence [2729]. In clinical practice, the presence of these polymorphisms is associated with the development of diseases such as cancer, diabetes, and coronary disease, in which an altered HIF-1α is observed in various groups among different populations [30–32].…”
Section: Discussionmentioning
confidence: 99%
“…The denaturation was at 95°C for 5 min, followed by 35 cycles of denaturation at 95°C for 30 sec, annealing at 61°C for 30 sec, extension at 70°C for 1 min, and a final extension at 72°C for 10 min. PCR products were purified and sequenced using Big Dye Terminator kit (version 3.1) on an ABI Prism® 3100 Automated DNA sequencer according to the manufacturer's protocol (Applied Biosystems, Foster City, CA) [34]. …”
Section: Methodsmentioning
confidence: 99%